Building a Process Driven Organization with the Process Normalization Technique - Václav Řepa (Complex Systems Informatics and Modeling Quarterly)
Despite the importance, the methodological standards for business process modeling are still very much insufficient. One of the most important aspects which must be covered with the process models is essential unity of object oriented and process oriented views of a business system. To achieve such unity, this article introduces a process normalization technique as part of the Methodology for Modeling and Analysis of Business Processes (MMABP). This technique is freely inspired by the famous 'ancient' Normalization of Data Structures technique which we regard as relevant and correct because of the essential unity of objects and processes in the business system. At the same time it can be seen that harmonizing the structure of processes with the (conceptual) structure of the Real World directly fulfills the objective. The goal of this article is to illustrate the steps of process normalization with examples. Important connected problems of structural algorithmic thinking, as well as other ways of manifesting the previously mentioned essential object-processes unity in the business system, are also discussed in the article.